2020
DOI: 10.1128/cmr.00190-19
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Antibacterial and Antifungal Therapies

Abstract: SUMMARY Intrathecal administration of anti-infectives is indicated in central nervous system infections by multiresistant pathogens when drugs that can reach adequate cerebrospinal fluid (CSF) concentrations by systemic therapy are not available. Antibiotics that readily pass the blood-brain and blood-CSF barriers and/or that have low toxicity allowing an increase in the daily dosage should not be used for intrathecal therapy. Intrathecal therapy is accompanied by systemic treatment. Antibacterials indispensab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 128 publications
(217 reference statements)
1
87
0
1
Order By: Relevance
“…SH‐SY5Y is the most commonly used model to study human neuron cells whereas PC12 and N27 are rat dopaminergic neural cell lines and CAD is a murine neuron cell line . The antibiotics used in our study are those that can penetrate blood brain barrier from six different classes: metronidazole (a nitroimidazole), tigecycline (a glycylcycline), azithromycin (a macrolide), clindamycin (a lincosamide), ampicillin (a β‐lactam) and sulfamethoxazole (a sulphonamide) . At clinically relevant concentrations, we found that metronidazole, tigecycline, clindamycin and azithromycin induced apoptosis of human primary neuron as assessed by flow cytometry of Annexin V (Figure A‐D).…”
Section: Resultsmentioning
confidence: 87%
“…SH‐SY5Y is the most commonly used model to study human neuron cells whereas PC12 and N27 are rat dopaminergic neural cell lines and CAD is a murine neuron cell line . The antibiotics used in our study are those that can penetrate blood brain barrier from six different classes: metronidazole (a nitroimidazole), tigecycline (a glycylcycline), azithromycin (a macrolide), clindamycin (a lincosamide), ampicillin (a β‐lactam) and sulfamethoxazole (a sulphonamide) . At clinically relevant concentrations, we found that metronidazole, tigecycline, clindamycin and azithromycin induced apoptosis of human primary neuron as assessed by flow cytometry of Annexin V (Figure A‐D).…”
Section: Resultsmentioning
confidence: 87%
“…For example, a case of meningitis by pandrug-resistant P. aeruginosa (with amikacin MIC 32 mg/L) was successfully treated with intraventricular amikacin [ 195 ]. PK/PD considerations for intrathecal administration of antibiotics are discussed in detail in a recent review [ 196 ]. Intravesical administration of antibiotics (e.g., colistin or aminoglycosides [ 197 , 198 ]) may also be an option for lower urinary tract infections, but clinical data against CAPT-resistant GNB are lacking.…”
Section: Pk/pd Considerations and Dosing Strategies For Overcoming Rementioning
confidence: 99%
“…7 Intrathecal and intraventricular antimicrobial therapy have been recommended by the Infectious Diseases Society of America in the treatment of adult health care-associated meningitis when the infection responds poorly to intravenous antibiotics, but evidence on intrathecal antimicrobial therapy in the pediatric population is scarce. 8,9 We present a case of pediatric standard-risk ALL with an unusually difficult P. aeruginosa infection, as well as a rationale for administering intrathecal antibiotics and pausing induction chemotherapy in the rare situation of an excellent day 15 minimal residual disease (MRD) response and persistent P. aeruginosa meningitis. Parental consent was obtained for the publication of this report.…”
Section: Intrathecal Tobramycin and Pausing Induction Chemotherapy For Pediatric Acute Lymphoblastic Leukemia Facilitate Successful Managmentioning
confidence: 99%